Formula Makanan Tradisional Bubur Kampiun Instan - Yulia Helmi Diza (Jurnal Litbang Industri, 2012)
The traditional food formula study of kampiun instant porridge had been carried out in three stages. Firstly, the optimization of the process to make filler of kampiun instant porridge, which consisted of instant mung beans, instant rice porridge, black glutinous rice porridge and banana instant. Secondly, preparation of sauce formula, and thirdly the mixing of fillers and formula sauce became a kampiun instant porridge. From the 8 (eight) formula, the F7 treatment that used E7 formula sauce (coconut milk powder instant : palmsuiker : sugar : milk were 1 : 0,5 : 0,5 : 0,25) tends to be preferred by the panelists. Nutrients and calories of kampiun instant porridge had good content of fat, protein and carbohydrates. Fat content of 5.70%-8.94%, protein content of 4.36%-20.46%, and carbohydrate content of 26.73%-32.61%. While the caloric value of 180.27 kcal-254, 62 kcal.  Therefore, the kampiun instant porridge can be used as an alternative for breakfast, emergency food for disaster-prone areas and specific food souvenirs of West Sumatra.ABSTRAKPenelitian formula makanan tradisional bubur kampiun instan telah dilakukan melalui tiga tahapan. Pertama, tahap optimasi proses pembuatan bahan pengisi bubur kampiun instan, yang terdiri dari kacang hijau instan, bubur beras instan, bubur ketan hitam instan dan pisang instan. Kedua, pembuatan formula kuah bubur kampiun instan, dan ketiga, pencampuran bahan pengisi dan formula kuah menjadi bubur kampiun instan. Dari 8 (delapan) formulasi, perlakuan F7 yang menggunakan formula kuah E7 (santan powder instan : palmsuiker : gula pasir : susu adalah 1 : 0,5 : 0,5 : 0,25) merupakan perlakuan yang cenderung lebih disukai oleh panelis. Dilihat dari kandungan gizi dan kalori, bubur kampiun instan mengandung lemak, protein dan karbohidrat yang baik. Kandungan lemak sebesar 5,70-8,94%, protein sebesar 4,36-20,46% dan karbohidrat sebesar 26,73-32,61%. Sedangkan nilai kalori sebesar 180,27- 254,62 kkal. Karena itu bubur kampiun instan ini dapat dimanfaatkan sebagai salah satu alternatif untuk sarapan pagi, makanan darurat untuk daerah rawan bencana dan sebagai makanan oleh-oleh khas Sumatera Barat.